Identity Conditions for transcendent Universals (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this work it is argued that it is not incoherent to attribute conditions ofidentity founded on causal powers to transcendent universals. After explaining some crucial notions of metaphysics of properties, it is said how conditions of identity for properties have been differentiated between so called “abundant properties” and “sparse properties”.
Keywords: Universals; Inmanent Universals; Transcendent Universals; Conditions of Identity; Causal Powers